2019
DOI: 10.1007/s11837-019-03715-1
|View full text |Cite|
|
Sign up to set email alerts
|

Selective Laser Melting of Al0.3CoCrFeNi High-Entropy Alloy: Printability, Microstructure, and Mechanical Properties

Abstract: Al 0.3 CoCrFeNi high-entropy alloy (HEA) was additively manufactured by powder-bed selective laser melting (SLM) with emphasis on its microstructure and tensile properties. Al 0.3 CoCrFeNi showed excellent printability, enabling fabrication of fully dense products. The microstructure of the SLM as-built HEA consisted of a single-phase disordered face-centered cubic solid solution with fine columnar grains elongated along the build direction. The characteristic features of the as-built microstructure were a <11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…Peyrouzet et al found that the an as‐printed SLM Al 0.3 CoCrFeNi HEA exhibits superior tensile strength (896 MPa) with decent ductility (≈29%) in comparison with the same alloy in as‐cast or wrought state. [ 110 ] Lin et al investigated the effect of the annealing temperature on the microstructure and mechanical properties of an SLM FeCoCrNi HEA. [ 102 ] The authors found that increasing the annealing temperature leads to a gradual decrease in yield strength and an increase in plasticity.…”
Section: Properties Of High‐entropy Alloys (Heas) Fabricated Via Slmmentioning
confidence: 99%
“…Peyrouzet et al found that the an as‐printed SLM Al 0.3 CoCrFeNi HEA exhibits superior tensile strength (896 MPa) with decent ductility (≈29%) in comparison with the same alloy in as‐cast or wrought state. [ 110 ] Lin et al investigated the effect of the annealing temperature on the microstructure and mechanical properties of an SLM FeCoCrNi HEA. [ 102 ] The authors found that increasing the annealing temperature leads to a gradual decrease in yield strength and an increase in plasticity.…”
Section: Properties Of High‐entropy Alloys (Heas) Fabricated Via Slmmentioning
confidence: 99%
“…The av erage dislocation density measured from BFTEM images, recorded from at least three distinct regions, was ~5 × 10 13 /m 2 . This value can be considered to lie in between the dislocation density of a fully recrystal lized/annealed metallic alloy (~10 11 /m 2 [36] ) and the typical disloca tion density reported in case of selectively laser melted (SLM) alloy sam ples (~10 14 /m 2 [37] ) . An additional factor that can result in a higher YS is the presence of fine scale cells or sub grain structures within the primary grains [38] .…”
Section: Resultsmentioning
confidence: 99%
“…For engineering alloys, the yield strength can be dictated by the strengthening factors like intrinsic lattice friction (σ LF ), solid solution strengthening (σ SSS ), grain boundary strengthening/Hall-Petch strengthening (σ HP ), dislocation strengthening (σ dislo ), and particle dispersion strengthening (σ disp ). The yield strength of the alloy can be predicted by using the formula given in the following equation [75,76,77,78,79]:…”
Section: Discussionmentioning
confidence: 99%
“…The remaining strength contributing factors (σ HP , σ dislo , and σ displ ) can be evaluated from Eqs. (3)-(5) [76].…”
Section: Discussionmentioning
confidence: 99%